DIAGNOSTICS OF DENDRITE STRUCTURE OF MULTICOMPONENT ALUMINUM ALLOYS - V. M. Golod; L. Yu. Dobosh (Литьë и металлургия, 2018)
Stages of system analysis and mathematical models for predicting the dendritic structure of multicomponent aluminum alloys are considered. Computer diagnostics of nonequilibrium crystallization is realized by the joint use of the apparatus of computational thermodynamics and means of computational heat transfer for solving problems of computational materials science. The results of modeling the evolution of the dendritic structure are presented with a change in the diffusion intensity in the solid phase from equilibrium conditions to complete suppression.